Alternative Translation of 1 Corinthians 12.2: Unreal (Contra-Factual) Sense of àn ḗgesthe apagómenoi - Lee, Yongbom (The Bible translator, 2014)
Many English translations follow Blass and Debrunner, taking ἂν ἤγεσθε ἀπαγόμενοι (1 Cor 12.2) in an iterative sense: “You know that, when you were pagans, you were (led astray) to mute idols, as you used to be led astray,” which makes little sense. In Classical and Hellenistic Greek, a past indicative verb is frequently used with the particle ἄν in a non-conditional clause, to indicate an unreal (contra-factual) sense in the past or the present. It makes better sense to translate ἂν ἤγεσθε ἀπαγόμενοι in an unreal (contra-factual) sense in the present—“but you are not led astray now!”